2007
DOI: 10.1016/j.ijrobp.2007.05.072
|View full text |Cite
|
Sign up to set email alerts
|

Response to Therapy and Outcomes in Oropharyngeal Cancer Are Associated With Biomarkers Including Human Papillomavirus, Epidermal Growth Factor Receptor, Gender, and Smoking

Abstract: IntroductionAppropriate treatment of advanced oral/oropharyngeal squamous cell carcinoma is a difficult challenge. Less than 50% of patients survive more than 5 years 1 . Surgery affects visible structures important for eating, swallowing, speaking, and human interaction. Organ sparing treatments can save important structures and can lead to improved outcome in patients who respond to such therapy. Induction chemotherapy followed by concurrent chemoradiation has shown efficacy both for organ sparing and surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
1
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(91 citation statements)
references
References 10 publications
6
82
1
2
Order By: Relevance
“…A further paper which supports these findings is that of Fakhry [8]. After adjustment for age, tumour stage, and ECOG performance status, tumour HPV status was also statistically significantly associated with progression free survival (Figure 4).…”
Section: Clinical Significance Of Hpv Positive Status In Head and Neck mentioning
confidence: 58%
See 1 more Smart Citation
“…A further paper which supports these findings is that of Fakhry [8]. After adjustment for age, tumour stage, and ECOG performance status, tumour HPV status was also statistically significantly associated with progression free survival (Figure 4).…”
Section: Clinical Significance Of Hpv Positive Status In Head and Neck mentioning
confidence: 58%
“…Data on molecular diagnostic tests was derived from general papers on the subject [5] and then specific papers on HPV detection. Certain conclusions in this dissertation were derived from constructing publications, particularly those by Kloazar [6], Kumar [7], Fakhry [8] and Weinberger [9].…”
Section: Methodsmentioning
confidence: 96%
“…In the last several years, the association between human papilloma virus (HPV) and head and neck cancer has been solidified (Wansom et al 2010, Albers et al 2005, Sirianni et al 2004, Sirianni, Wang and Ferris 2005, Kumar et al 2007, Kumar et al 2008, Sisk et al 2002. Interestingly, HPV associated head and neck cancers exhibit better prognosis and appear to respond better to chemo-radiation.…”
Section: Other Modifications In Cancermentioning
confidence: 99%
“…HR-HPV infection is an independent prognostic indicator (Weinberger et al, 2006;Kumar et al, 2007;Fakhry et al, 2008;Gillison et al, 2000;Hafkamp Kuo et al, 2008;Worden et al, 2008;Lill et al, 2011;Posner et al, 2011). Kuo and colleagues reported that the 5-year overall survival rate of patients with HR-HPV positive OSCC was 89%, which was significantly higher than HR-HPV negative patients (61%, p=0.001) (Kuo et al, 2008).…”
Section: Introductionmentioning
confidence: 99%